Economic viability of yield monitoring systems in potato farming : a comparative study between New Zealand and India : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agribusiness at Massey University, School of Agriculture and Environment, Palmerston North, New Zealand - Kodali, Praneeth Rayudu (Massey University, 2025)
India is one of the largest global producers of potatoes by volume. At the same time, New Zealand, with its significantly smaller land area and farming population, consistently achieves higher yields, better produce quality, and greater per-hectare productivity. This study investigates the economic viability of adopting Yield Monitoring Systems (YMS) in potato farming across both countries to determine whether such precision agriculture technologies can enhance profitability and efficiency in India. The research draws on secondary data from official sources, including Potato New Zealand and the Government of India, covering regional potato yields in Canterbury, Pukekohe, and Manawatu (NZ), and six Indian states. Using economic evaluation metrics—Return on Investment (ROI), Payback Period (PP), and Cost-Benefit Ratio (CBR)—the study compares outcomes across two adoption models: individual farmer-based adoption and service-based adoption via contractors or Farmer Producer Organisations (FPOs). Findings reveal that while YMS significantly improves farm-level profitability and efficiency in New Zealand due to larger landholdings and advanced mechanisation, direct replication of this model in India is economically unfeasible for smallholder farmers. The high initial investment, lack of economies of scale, post-harvest losses, and limited access to institutional credit act as significant barriers. The study concludes that for YMS to be viable in India, adaptation is essential—either through modular integration of YMS into existing machinery or via collective access through FPOs and Custom Hiring Centres. This comparative analysis offers a pathway for scalable YMS adoption in India, promoting precision agriculture not by direct transfer but through context-specific adaptation, institutional support, and strategic policy reallocation.
Keywords: Yield Monitoring Systems (YMS); Precision Agriculture; Economic Viability; Cost-Benefit Ratio (CBR); Return on Investment (ROI); Payback Period (PP); Potato Farming; New Zealand Agriculture; India Agriculture; Smallholder Farmers; Farmer Producer Organisations (FPOs); Custom Hiring Centres (CHCs); Agricultural Policy; Cooperative Farming Models; Digital Agriculture; Scale Economies in Agriculture; 300208 Farm management, rural management and agribusiness